Awareness of cervical cancer and screening in Benin and Cameroon: an analysis of the Demographic and Health Survey, 2017-2018 - Nike A Olajide; Bhautesh D Jani; Claire L Niedzwiedz; Cathy Johnman; Kathryn A Robb (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Cervical cancer incidence and mortality are high in Africa. We assessed cervical cancer and screening awareness in two West African countries. # Methods We used data from the Demographic and Health Surveys (DHS) in Benin (2017-2018) and Cameroon (2018). Women (n=21322) aged 15-49 were interviewed on awareness of cervical cancer and cervical cancer screening. Descriptive statistics and logistic regression analysis were employed. # Results Awareness of cervical cancer was low among women in Cameroon (46.1%) and very low in Benin (9.5%). Among those aware of cervical cancer, 51.4% in Benin and 59.7% in Cameroon were also aware of cervical screening. In the adjusted analysis, women in Cameroon aged 45+ had the highest awareness odds of both cervical cancer (adjusted odds ratio, aOR=2.91, 95% confidence interval, CI=2.36-3.60) and screening (aOR=1.75, 95% CI=1.33-2.29). In Benin, women aged 45+ had the highest cervical cancer awareness (aOR=1.89, 95% CI=1.23-2.91) while screening awareness was highest in women aged 25-34 years (aOR=1.98, 95% CI=1.20-3.27). Women with higher education were six to nine times more aware of cervical cancer and three to four times more aware of cervical screening than women with no education in Benin and Cameroon respectively. Additionally, cervical cancer awareness was approximately four times higher in the richest wealth quintile in Cameroon. In Benin, the odds of awareness of cervical cancer were increased with daily internet use (aOR=3.61, 95% CI=2.45-5.32) and radio listening once a week (aOR=1.73, 95% CI=1.04-2.88) compared to no internet and no radio listening respectively. In Cameroon, both awareness of cervical cancer and screening increased with daily internet use (aOR=1.95, 95% CI=1.61-2.35) and (aOR=1.35, 95% CI=1.10-1.67) respectively. # Conclusions There is a need to increase awareness of cervical cancer and screening in Benin and Cameroon and extend to other West African countries. The internet and radio appear to be important potentially effective means for raising awareness.